PENGARUH CUSTOMER ACCOUNTING SEBAGAI STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES DAN CUSTOMER ORIENTATION TERHADAP ORGANIZATIONAL PERFORMANCE - Lisa, Valentine (Business Accounting Review, 2015)
This Study was done to examine the affect of customer accounting as Â strategic management accounting techniques and customer orientation to organizational performance. This study used primary data from questionnaires which were distributed to 50 manufacturing companies in Surabaya and Sidoarjo. The data collected would be analyzed by using Partial Least Square method to test the hypothesis. The result showed there were positive and significant influence from customer accounting and customer orientation to organizational performance.